IMPLEMENTASI MEDIA CARD SORTING UNTUK MEMBENTUK SIKAP KERJASAMA SISWA DALAM PEMBELAJARAN IPA DI MI - aulia_ainur_rofiq; Khosiah, Nur (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2024)
Education is a critical determinant of a nation's intellectual development and plays a pivotal role in enhancing the skills and capabilities of its human resources. However, a lack of collaboration or teamwork among students during discussions often hinders the learning process from achieving its intended outcomes. This study aims to identify media that can foster students' cooperative attitudes. The research employs a descriptive method with a qualitative approach, seeking to describe the application of the card sorting media in promoting students' collaborative attitudes during science lessons at MI Nurul Islam Mayangan. The study participants consist of all 15 fifth-grade students at MI Nurul Islam. The implementation of science lessons using card sorting media has proven highly effective, as evidenced by the students' engagement and active participation during the activities. The findings indicate that the use of card sorting media in science learning at MI Nurul Islam positively impacts students, particularly by enhancing their collaboration and active involvement. Based on these findings, it is recommended that teachers integrate card sorting media more frequently in their lessons to support the development of students' cooperative attitudes, especially in science subjects.